2020
DOI: 10.3847/1538-4357/ab6604
|View full text |Cite
|
Sign up to set email alerts
|

The Lyman Continuum Escape Survey. II. Ionizing Radiation as a Function of the [O iii]/[O ii] Line Ratio

Abstract: We discuss the rest-frame optical emission line spectra of a large (∼ 50) sample of z ∼ 3.1 Lyman alpha emitters (LAEs) whose physical properties suggest such sources are promising analogs of galaxies in the reionization era. Reliable Lyman continuum escape fractions have now been determined for a large sample of such LAEs from the Lyman Continuum Escape Survey (LACES) undertaken via deep HST imaging in the SSA22 survey area reported in Fletcher et al. (2019). Using new measures of [O ii] emission secured from… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
100
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(113 citation statements)
references
References 74 publications
9
100
4
Order By: Relevance
“…[O ]/[O ] line-ratio has been considered a promising indicator of LyC leakage as it might trace density-bounded nebulae (e.g.,Jaskot & Oey 2013;Nakajima & Ouchi 2014) and has been extensively studied due to the relative brightness of both emission-lines. However, tests of this indicator have produced mixed results (e.g.,Naidu et al 2018;Chisholm et al 2018;Jaskot et al 2019;Bassett et al 2019;Nakajima et al 2020). On the other hand, we identify a stark contrast in [O ]/[O ] across our stacks of LAEs ( §5).…”
mentioning
confidence: 64%
See 2 more Smart Citations
“…[O ]/[O ] line-ratio has been considered a promising indicator of LyC leakage as it might trace density-bounded nebulae (e.g.,Jaskot & Oey 2013;Nakajima & Ouchi 2014) and has been extensively studied due to the relative brightness of both emission-lines. However, tests of this indicator have produced mixed results (e.g.,Naidu et al 2018;Chisholm et al 2018;Jaskot et al 2019;Bassett et al 2019;Nakajima et al 2020). On the other hand, we identify a stark contrast in [O ]/[O ] across our stacks of LAEs ( §5).…”
mentioning
confidence: 64%
“…Behrens et al 2019;Smith et al 2019Smith et al , 2021. It is plausible that a Ly𝛼-selected sample picks out only galaxies viewed at favorable angles, which might minimize the scatter between 𝑓 esc and galaxy properties reported in previous studies (e.g., Fletcher et al 2019;Nakajima et al 2020;Tang et al 2021). Alternatively, it is possible that the Ly𝛼 pre-selection selects for "hidden" parameters that otherwise add scatter to such correlations as well, e.g., the presence of outflows or the relatively low mass of LAEs (e.g.…”
Section: Implications For Constraining Lyc 𝑓 Esc With Jwst: Can Strong Lines Do It All?mentioning
confidence: 99%
See 1 more Smart Citation
“…Nev ertheless, there hav e been many situations where simulations have agreed on emission-line properties of high-redshift galaxies and provide deep insights into or predictions of the early Univ erse. F or e xample, the necessary but insufficient condition that LyC leakers have high O32 (Barrow et al 2020 ;Katz et al 2020b ) as confirmed at z ∼ 2-3 (Nakajima et al 2020 ) or the strong [O I ] 63 μm (hereafter [O I ]) emission line (Olsen et al 2017 ;Katz et al 2019b ), that was recently observed at z > 6 (Rybak et al 2020 ).…”
mentioning
confidence: 90%
“…Constraining the LyC escape fraction as a function of both redshift and galaxy properties has been the subject of numerous observational and theoretical studies as constraining this parameter will allow for the determination of both the reionization history and the primary sources responsible (e.g. Nakajima et al 2020;Kimm et al 2017;Barrow et al 2020). While the global, luminosity-weighted escape fractions cannot be substantially different between the simulations with different PMFs because of the observed consistency in star formation and reionization histories, we may expect slight differences due to the variations in ISM properties.…”
Section: Impact Of Primordial Magnetic Fields On the Lyc Escape Fractionmentioning
confidence: 99%